Phylogeny of the nominotypical subgenus of Culex (Diptera: Culicidae): insights from analyses of anatomical data into interspecific relationships and species groups in an unresolved tree. Issue 4 (4th July 2017) - Harbach, Ralph E.; Culverwell, C. Lorna; Kitching, Ian J.
Abstract : The aim of this study was to produce the first objective and comprehensive phylogenetic analysis of the speciose subgenus Culex based on morphological data. We used implied and equally weighted parsimony methods to analyse a dataset comprised of 286 characters of the larval, pupal, and adult stages of 150 species of the subgenus and an outgroup of 17 species. We determined the optimal support by summing the GC supports for each MPC, selecting the cladograms with the highest supports to generate a strict consensus tree. We then collapsed the branches with GC support < 1 to obtain the 'best' topography of relationships. The analyses largely failed to resolve relationships among the species and the informal groups in which they are currently placed based on morphological similarities and differences. All analyses, however, support the monophyly of genus Culex . With the exception of the Atriceps Group, the analyses failed to find positive support for any of the informal species groups (monophyly of the Duttoni Group could not be established because only one of the two species of the group was included in the analyses). Since the analyses would seem to include sufficient data for phylogenetic reconstruction, lack of resolution appears to be the result of inadequate or conflicting character data, and perhaps incorrect homology assessments. Molecular and other biological data are needed to gain insights into the evolution of subgenus Culex . Nevertheless, we discuss the placement of several taxa in the current morphology-based classification of the subgenus based on insights realized during the study.